Inhibition of homologous recombination repair by Mirin in ovarian cancer ameliorates carboplatin therapy response in vitro - Horak, Josef; Vallusova, Dominika; Cumova, Andrea; Holy, Petr; Vodicka, Pavel; Opattova, Alena (Mutagenesis, 2025)
Chemoresistance poses one of the most significant challenges of cancer therapy. Carboplatin (CbPt) is one of the most used chemotherapeutics in ovarian cancer (OVC) treatment. MRE11 constitutes a part of homologous recombination (HR), which is responsible for the repair of CbPt-induced DNA damage, particularly DNA crosslinks. The study's main aim was to address the role of HR in CbPt chemoresistance in OVC and to evaluate the possibility of overcoming CbPt chemoresistance by Mirin-mediated MRE11 inhibition in an OVC cell line. Lower expression of MRE11 was associated with better overall survival in a cohort of OVC patients treated with platinum drugs (TCGA dataset, P < 0.05). Using in vitro analyses, we showed that the high expression of HR genes drives the CbPt chemoresistance in our CbPt-resistant cell line model. Moreover, the HR inhibition by Mirin not only increased sensitivity to carboplatin (P < 0.05) but also rescued the sensitivity in the CbPt-resistant model (P < 0.05). Our results suggest that MRE11 inhibition with Mirin may represent a promising way to overcome OVC resistance. More therapy options will ultimately lead to better personalized cancer therapy and improvement of patients' survival.
Keywords: Gene Expression Regulation, Neoplastic; poškození DNA; protinádorové látky; MRE11 Homologue Protein; DNA Damage; Cell Line, Tumor; Ovarian Neoplasms; regulace genové exprese u nádorů; Carboplatin; chemorezistence; Recombinational DNA Repair; karboplatina; nádory vaječníků; rekombinační oprava DNA; lidé; ženské pohlaví; Humans; Drug Resistance, Neoplasm; nádorové buněčné linie; Female; homologní protein MRE11; Antineoplastic Agents